Mental health impacts of early marriage on mothers caring for stunted toddlers - Suherman, Suherman; Putri, Nella Amallia (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2026)
Background: Stunting remains a significant health concern, both nationally and globally. One of the factors contributing to stunting is early marriage. This not only impacts the physical condition of the mother and child, but also impacts the mother’s mental health, especially in caring for stunted toddlers. Objective: This study aims to explore the subjective experiences of mothers who married at an early age and understand the mental health impacts they experience in caring for stunted children in Tanjung Gunung in 2025. Method: This study employed a qualitative approach using a phenomenological design. The total number of participants was six, consisting of four mothers who were involved in early marriage, one village head, and one head of the community health center (Puskesmas). Results: The results of this study revealed seven main themes that collectively describe the experiences of mothers who entered marriage at an early age. Theme 1: Reasons for early marriage show that such marriages often occur due to accidental circumstances, economic factors, and the influence of love at a young age. Theme 2: changes in roles after marriage highlights the rapid transition young women face as they take on responsibilities as wives and mothers. Theme 3: challenges after marriage, identifies economic hardship as the main difficulty in managing household needs. Theme 4: pressure from psychological and emotional problems, indicates that mothers often experience stress and emotional strain due to limited coping abilities and a lack of support. Theme 5: child development and growth, reveals that children of young mothers are more prone to malnutrition and stunting. Theme 6: social support in dealing with mothers’ mental health emphasizes the crucial role of emotional and family support in maintaining mental well-being. Theme 7: The meaning of early marriage for mothers shows that some mothers feel regret, while others find hope and personal growth from their experience. Overall, these themes illustrate that early marriage presents both social and emotional challenges, affecting the personal, psychological, and family aspects of young mothers’ lives. Conclusion: Early marriage has complex impacts on the lives of young mothers, encompassing psychological, social, and economic aspects. Young women who marry at an early age experience rapid role transitions, emotional pressure, and challenges in meeting family needs while supporting their children’s growth and development. However, some of them can find positive meaning and hope through these experiences. Therefore, this study emphasizes the importance of psychosocial support, reproductive health education, and economic empowerment for adolescents and young mothers as both preventive and curative measures to minimize the negative effects of early marriage.